Somerville for women : an Oxford college, 1879-1993 - Adams, Pauline (Oxford University Press, 1996)
Somerville for Women is the first history to appear for 75 years of the pioneering Oxford women's college whose alumnae include a Nobel prize-winner for chemistry, two prime ministers, and a whole school of novelists. As an account of the strategies adopted by an academic community of women, first to gain acceptance by a male university, and then to survive within a mixed one, it is a domestic history of much more than domestic interest. Drawing on a rich archive, and a wide range of published sources, it provides significant insights into the history of the University and touches on many aspects of women's studies. The concluding account of the circumstances leading in 1992 to the controversial decision to admit men raises a number of issues of importance for higher education in general and Oxford in particular.